2021
DOI: 10.1017/s0950268821001230
|View full text |Cite
|
Sign up to set email alerts
|

The challenging task to select Salmonella target serovars in poultry: the Italian point of view

Abstract: According to the EFSA and ECDC annual report, human salmonellosis is mostly related to consumption of contaminated poultry products. Since 2003 in Europe, the Salmonella serovars considered relevant for human health and subject to control in breeding hens of Gallus gallus are: S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 8 publications
2
22
0
Order By: Relevance
“…All these data confirm how control measures must be maintained constantly and cannot be reduced, in order to avoid the spread of the pathogen. Indeed, in‐depth evaluations of epidemiological situations at local level could provide suggestions for the appropriate allocation of resources, in order to achieve a lower number of positive flocks and ultimately a reduced number of human salmonellosis cases, with an undoubted benefit at EU level (Leati et al., 2021 ).…”
Section: Salmonellamentioning
confidence: 99%
“…All these data confirm how control measures must be maintained constantly and cannot be reduced, in order to avoid the spread of the pathogen. Indeed, in‐depth evaluations of epidemiological situations at local level could provide suggestions for the appropriate allocation of resources, in order to achieve a lower number of positive flocks and ultimately a reduced number of human salmonellosis cases, with an undoubted benefit at EU level (Leati et al., 2021 ).…”
Section: Salmonellamentioning
confidence: 99%
“…In 2020, the top five Salmonella serovars involved in human infections in Europe were S. Enteritidis, S. Typhimurium, monophasic S. Typhimurium (1,4,[5],12:i:-), S. Infantis, and S. Derby [EFSA and ECDC (European Food Safety Authority and European Centre for Disease Prevention and Control), 2021]. In Italy however, S. Napoli ranks among the top serovars causing human infections even though it is relatively uncommon in other European countries (Leati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, Salmonellosis was the second most reported zoonosis in 2020 with 52,702 cases of illness and was an important cause of foodborne outbreaks mainly associated with the consumption of eggs and eggs products, bakery products and pig meat and products thereof [ EFSA and ECDC (European Food Safety Authority and European Centre for Disease Prevention and Control), 2021 ]. In Italy, with more than 3,000 human cases reported per year [ EFSA and ECDC (European Food Safety Authority and European Centre for Disease Prevention and Control), 2021 ], Salmonellosis is the most common foodborne infection ( Leati et al, 2021 ). The genus Salmonella includes two species, Salmonella ( S. ) bongori and S. enterica , and six subspecies: enterica I, salamae II, arizonae IIIa, diarizonae IIIb, houtenae IV, and indica VI.…”
Section: Introductionmentioning
confidence: 99%
“…Hadar in 2019 in the EU ( ECDC, n.d. ). Based on epidemiological evidences collected in Italy, Leati et al (2021) suggested that other serotypes, such as Salmonella Derby and Salmonella Napoli, should be considered for control at primary production level, due to their frequent isolation in human infections. In addition, it has increasingly been reported that specific clones of different serotypes, rather than the serotype as such, are responsible for emergent spread in both humans and the food chain ( Coipan et al, 2020 ; García-Soto et al, 2020 ; Mastrorilli et al, 2020 ; EFSA and ECDC, 2021b ).…”
Section: Introductionmentioning
confidence: 99%